The Relationship Between Quotient and Employee Performance (Study at the Subdistrict Office and District Office in the Kelapa Lima District, Kupang City Government) - Asmawati; Jefirstson Richset Riwukore; Marzuki Alie; Tien Yustini; Yolanda Yuniarti Hutajulu (Institute of Computer Science (IOCS), 2022)
This research aimed to analyze and prove the effect and contribution of quotient to employee performance using dimensions of intellectual, emotional, spiritual, and adversity. This research was carried out for 5 months from February to June 2022 at the Subdistrict Office and District Office in the Kelapa Lima District, Kupang City. This research is classified as quantitative research. The research population was 120 employees who were determined by the sample of respondents using a saturated sample (non-probability sampling) so that the entire population became research respondents. The types of data used are primary and secondary data obtained by questionnaire, observation, and documentation techniques. Data analysis used multiple linear regression analysis. The results showed that the intellectual quotient variable had a positive and significant effect on employee performance because it had t-count > t-table (9,047 > 1.98027) on Sig. Prob. 0.000 < α 0.05. Emotional quotient variable has a positive and significant effect on employee performance because the value of t-count > t-table (3,004 > 1,98027) in Sig. Prob. 0.003 < α 0.05. The spiritual quotient variable has a positive and significant effect on employee performance because the t-count > t-table (2.953 > 1.98027) in Sig. Prob. 0.004 < α 0.05, and the adversity quotient variable has a positive and significant effect on employee performance because the t-count > t-table (3.054 > 1.98027) on Sig. Prob. 0.003 < α 0.05. Simultaneously, the quotient variable with the lowest value on employee performance is intellectual quotient (54.3%), emotional quotient (20.3%), adversity quotient (19.7%), and spiritual quotient (16.7 %).